IR spectrometric method for recording structural-phase transformations in thin films of cryovacuum condensates - Shinbayeva, A.K.; Aldiyarov, A.U.; Drobyshev, A.S.; Nurmukan, A.E. (Recent Contributions to Physics, 2018)
A method for recording structural-phase transformations in cryovacuum gas condensates is described. The method is based on IR spectrometric measurements in combination with obtaining thermograms at a fixed observation frequency. The sample condenses at a fixed temperature. Further, on the basis of previously obtained temperature-discrete spectral measurements, the value of the frequency most sensitive to changes in the nature and position of the absorption band is determined. After that, the value of the spectrometer is set at one of the observation frequencies and a continuous heating of the sample begins until its evaporation with simultaneous measurement of the spectrometer signal. Based on the obtained thermograms, the temperature intervals in which the absorption spectra are transformed are determined. Using the data of direct structural measurements of other authors, conclusions are drawn regarding thermostimulated structural transformations in the sample under study.
Keywords: Cryovacuum condensates, IR spectra, methods